Amphetamine abuse in Sweden: subject demographics, changes in blood concentrations over time, and the types of coingested substances - Jones, Alan Wayne; Holmgren, Anita (Journal of clinical psychopharmacology, 2013)
Amphetamine is a major drug of abuse in Sweden and in the other Nordic countries. The demographics of amphetamine abusers in Sweden and the concentrations of this stimulant in blood are reported for 10 years of forensic blood samples (2001-2010). Using a forensic toxicology database (TOXBASE), we studied 1183 amphetamine-related deaths, 20,452 users of illicit drugs, and 47,366 people arrested for driving under the influence of drugs (DUID). Most amphetamine abusers were male (82%-87%), and their average age was 33 to 39 years with males being 2 to 3 years older than females (P < 0.001). Mean (median) concentrations of amphetamine in blood were 1.25 (0.40) mg/L in autopsy cases, 0.61 (0.40) mg/L in users of illicit drugs, and 0.76 (0.58) mg/L in DUID suspects. Median concentration in DUID suspects was significantly higher than in the other forensic materials (P < 0.001). Women also had higher median concentrations of amphetamine in blood than male abusers of this central stimulant (P < 0.001). The major coingested drugs were benzodiazepines (41%), cannabis (26%), opiates (21%), and alcohol (18%) in autopsy cases. Polydrug use was less common in DUID suspects and users of illicit drugs, although benzodiazepines (13%), tetrahydrocannabinol (12%), and opiates (5%) were often identified along with amphetamine. Because median concentration of amphetamine was higher in living subjects (DUID suspects) compared with amphetamine-related deaths, this points toward toxicity of coingested drugs or adverse drug-drug interaction as being responsible for death.